THE ROLE OF TELEMEDICINE IN THE DIAGNOSIS OF PATIENTS WITH COMBINED INJURIES OF THE MAXILLOFACIAL SKELETON - Bakiyeva SH.X.,; Karimberdiyev B.I,; Djurayev J.A, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  Combined  injuries  of  the  maxillofacial  skeleton  require  rapid  and accurate  diagnosis  to  ensure  timely  treatment  and  prevent  complications.  In  recent years,  telemedicine  has  become  an  important  tool  in  trauma  diagnostics,  enabling remote consultation, image sharing, and specialist involvement. This study evaluates the  role  of  telemedicine  in  the  diagnostic  process  of  patients  with  combined maxillofacial injuries. A total of 140 patients were analyzed using clinical examination, radiological  imaging,  and  telemedicine-based  consultation  systems.  The  results demonstrated that telemedicine significantly improves diagnostic accessibility, reduces time to diagnosis, and enhances the accuracy of clinical decision-making. The study confirms that telemedicine is an effective supplementary tool in the management of maxillofacial trauma, especially in emergency and remote healthcare settings.